1994
DOI: 10.1159/000178205
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of Capillary Endothelial Cells Contributes to Traumatic Hemorrhagic Shock-Induced Microvascular Injury: A Morphologic and Morphometric Analysis

Abstract: The endothelial cell (EC) response during the first 2 h after traumatic hemorrhagic shock (THS) was analyzed in the rat mesentery by electron microscopy. Using a computer-assisted image analysis system, we interactively measured THS-induced changes of the area and the mean height of EC as well as the number of swollen EC occluding the capillary lumen. Analysis distinguished between capillaries presenting with the lumen blocked by corpuscular blood cells and capillaries with an open lumen. THS resulted in a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(14 reference statements)
1
14
0
1
Order By: Relevance
“…lactacidosis; bovine aortic endothelial cells; pH regulation CAPILLARY DIAMETERS under pathophysiological conditions may be reduced below those of the traversing undeformed red and white blood cells (16) and, therefore, may jeopardize cell passage through the microcirculation as well as nutritive blood flow. The major cause of the reduction of capillary patency is endothelial swelling, as observed in hemorrhagic shock (14,16) or systemic blood acidosis, but not at low flow conditions per se (15). Swelling in these experiments could be prevented by amiloride analogs, as an indication that a Na ϩ /H ϩ exchanger (NHE) participates in the swelling process.…”
mentioning
confidence: 78%
“…lactacidosis; bovine aortic endothelial cells; pH regulation CAPILLARY DIAMETERS under pathophysiological conditions may be reduced below those of the traversing undeformed red and white blood cells (16) and, therefore, may jeopardize cell passage through the microcirculation as well as nutritive blood flow. The major cause of the reduction of capillary patency is endothelial swelling, as observed in hemorrhagic shock (14,16) or systemic blood acidosis, but not at low flow conditions per se (15). Swelling in these experiments could be prevented by amiloride analogs, as an indication that a Na ϩ /H ϩ exchanger (NHE) participates in the swelling process.…”
mentioning
confidence: 78%
“…Endothelial cell swelling is a phenomenon observed in ischemia 21,22 and lactacidosis. 23 It is based on the activation of the plasma membrane Na ϩ /H ϩ exchanger inhibited by amiloride analogues as ethylisopropylamiloride.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have found that it is the acidotic nature of the blood, and not the reduction in blood flow per se, which is responsible for cell swelling in the models of low-flow ischemia we investigated ( fig. 2) [7], Swollen capillary endothelium has been demonstrated in skeletal muscle after complete ischemia [14] and in mesentery after a combined trauma and hemorrhagic shock insult [5], This latter study just published conclud ed that endothelial cells swell in capillaries with an open lumen (mean endothelial height increase of about 70%), but not in capillaries with the lumen blocked by blood cells (no perfusion). It seems unlikely, as the authors spec ulate, that rigid RBCs keep the lumen open.…”
Section: Discussionmentioning
confidence: 99%
“…Swelling of the endothelium with encroachment into the vessel lumen has been shown for capillaries in skeletal muscle [2][3][4] and mesentery [5] during hemorrhagic shock (global low-flow ischemia). The acute decrease in luminal diameter would increase hydraulic flow resistance, thereby hindering re flow efforts.…”
Section: Introductionmentioning
confidence: 99%